2023
DOI: 10.3390/molecules28020835
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and Anticancer Activity of Mono- and Polyfloral Moroccan Bee Pollen by Characterizing Phenolic and Volatile Compounds

Abstract: Bee pollen is frequently characterized as a natural source of bioactive components, such as phenolic compounds, which are responsible for its pharmaceutical potential and nutritional properties. In this study, we evaluated the bioactive compound contents of mono- and polyfloral bee pollen samples using spectroscopic and chromatographic methods and established links with their antioxidant and antitumor activity. The findings demonstrated that the botanical origin of bee pollen has a remarkable impact on its phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
2
14
0
1
Order By: Relevance
“…Some of the compounds found in the current research have already been identified in different samples. For instance, p-coumaric (0.20 mg/g) and caffeic (0.15 mg/g) acids were determined in monofloral Moroccan bee-collected pollen samples originating from Apiaceae and Fabaceae plants, respectively [41]. Furthermore, similar to the current research, the authors found different quercetin and kaempferol glycosides (ranging from 1.19 to 1.77 mg/g) as predominant compounds [41].…”
Section: Uhplc Phenolic Profile Of Pbpsupporting
confidence: 82%
See 1 more Smart Citation
“…Some of the compounds found in the current research have already been identified in different samples. For instance, p-coumaric (0.20 mg/g) and caffeic (0.15 mg/g) acids were determined in monofloral Moroccan bee-collected pollen samples originating from Apiaceae and Fabaceae plants, respectively [41]. Furthermore, similar to the current research, the authors found different quercetin and kaempferol glycosides (ranging from 1.19 to 1.77 mg/g) as predominant compounds [41].…”
Section: Uhplc Phenolic Profile Of Pbpsupporting
confidence: 82%
“…For instance, p-coumaric (0.20 mg/g) and caffeic (0.15 mg/g) acids were determined in monofloral Moroccan bee-collected pollen samples originating from Apiaceae and Fabaceae plants, respectively [41]. Furthermore, similar to the current research, the authors found different quercetin and kaempferol glycosides (ranging from 1.19 to 1.77 mg/g) as predominant compounds [41]. In a polyfloral sample consisting mostly of Cytisus stratius and Eucalyptus sp.…”
Section: Uhplc Phenolic Profile Of Pbpmentioning
confidence: 99%
“…The most accurate method for determining the botanical sources of HBP is palynological analysis (Li et al., 2018). Through pollen analysis, most researchers classified HBP as multifloral or monofloral (Alimoglu et al., 2021; Aylanc et al., 2023; Gercek et al., 2021). However, Barth et al.…”
Section: Resultsmentioning
confidence: 99%
“…The most accurate method for determining the botanical sources of HBP is palynological analysis (Li et al, 2018). Through pollen analysis, most researchers classified HBP as multifloral or monofloral (Alimoglu et al, 2021;Aylanc et al, 2023;Gercek et al, 2021). However, Barth et al (2010), Mosić et al (2019), and Nandi and Karmakar (2018) proposed a more detailed classification, covering mono, bi, tri, and multifloral categories.…”
Section: Palynological Verificationmentioning
confidence: 99%
See 1 more Smart Citation